3D data life in Cesis medieval castle in Latvia - Kalinka, Maris; Eriņš, Ingars; Vaivode, Viktorija; Goldbergs, Lauris; Korna, Ieva; Smirnovs, Rolands; Gorovojs, Kirils (International Conference “Environmental Engineering”, 2023)
This paper presents the lifecycle of 3D data in cultural heritage sites with a long-term and cyclical renovation process. 3D data is obtained in different periods with different sensors – ground laser scanning, drones, photographies of eralies period and simple measurements. In cultural and historical heritage objects, restoration works are carried out seasonally and in the conditions of available financing. 3D data and its supplementary data have much wider applicability beyond restoration or monitoring works. The data can be transferred to tourism, where it is used both for virtual reality (VR) or augmented reality (AR) technologies, and for the restoration using the HBIM approach. Thus, the data is transferred for re-use for restoration, tourism, and object management. The article discusses the acquisition, processing and application of 3D data for the creation of HBIM with the possibility of use in VR/AR equipment. This paper also examines the issue of updating data after restoration works, covering solutions for data publication. The aim of this work is to diversify the use of data in the long term without re-documenting full objects.
Keywords: laser scanning; photogrammetry; HBIM; virtual reality; augmented reality